Israeliyyatin The Story of The Son of The Prophet Ibrahim.: Comparative Study of The Interpretation of Surah As-Saffat 99-113 By Mufassir From Classical to Contemporary Eras - Rumaisah Murobbiyah Auliya (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Many commentators have narrated israeliyyat in their commentaries. Among these narrations, there is an israeliyyat that is correct according to creed, Islamic law, and historical reality, and some are not. Israiliyyat is widely used in interpreting verses, especially those related to the stories of the prophets and the previous people, including the story of the slaughter of the son of the Prophet Ibrahim, which is very popular among Muslims. Disputes in the story of Prophet Ibrahim and the son who is slaughtered lie in who the son is. This dispute has existed since the era of friends. Through a literature review of various books of commentary, the author tries to reveal the history of israiliyyat that influences the interpretation of the story. The author found three opinions from the commentators, namely that those slaughtered were Isma'il, and Ishaq, and opinions that silence this debate. The opinion that says Isma'il, who was slaughtered, is considered more logical and superior in terms of narration. In addition, the author finds a falsified history and changes to the Torah text in interpreting this story.